Loyalty, Exit, and Enforcement: Evidence from a Kenya Dairy Cooperative - Casaburi, Lorenzo; Macchiavello, Rocco (American Economic Review, 2015)
Organizations depend on members' “loyalty” for their success. Studying a cooperative's attempt to increase deliveries by members, we show that the threat of sanctions leads to highly heterogeneous response among members. Despite the cooperative not actually enforcing the threatened sanctions, positive effects for some members persist for several months. Other members “exit,” stopping delivering altogether. Among non-compliant members we document substantial heterogeneity in beliefs about the legitimacy of the sanctions. This lack of common understanding highlights the role played by managers in organizations and provides a candidate explanation for lack of sanctions enforcement documented by Ostrom (1990) and other studies.